Sex ed aid a how-to video production engaging parents to communicate sex education to their teenage children - Petrache, Ria Gene J.
Sex at its best is too marvelous a thing to be a attained casually and indiscriminately. It requires full openness and intimate fusion between two persons, and one does not want to be intimate with just anybody (stone and Church). Accessibility of information about sex education is made available to teens in almost every form ? be it on print, audio or video. This evolution in information dissemination can both be taken positively and negatively by parents who have the initial responsibility in providing what these sources can give to their teenage children. However, in the Philippines, this is hindered by traditions and beliefs causing parents to hold back and feel embarrassed about sex education. This production thesis answers the design problem: how to utilize the elements of drama in projecting the communication scenarios between teens and parents involving the topics on sex education? Gaining information through thorough library and online research with a corresponding interview conducted with parents and teens molded the formation and completion of the essential parts of the 1- minute PSA and the 3-minute How-to video. Furthermore, these projects were guided by the elements of drama name, (1) Plot, (2) Characters (3) Genre, (4) Theme and (5) Style. The procedure followed in the conceptual framework is as follows: Research and Analysis, Video Production Structure and Video-Editing. Since this study resulted to 2 video productions, the first one, which is a PSA is dedicated to projecting awkward scenes between parents and teens involving topics and images about sex education. This tactic is seen as an effective strategy in invoking the parents' interests and encouraging them to break the barrier about the said topic most especially when their teenage children need them the most. The PSA is basically a compilation of 3 awkward scenes including a scenario between 2 parents, a mother and her daughter and a father and his son. The 3-minute how-to video begins with a scene of a teenage boy reading a pornographic magazine. This is to send a message that if parents don't talk teens about sex education, teens will most likely resort to other sources ? peers and media. After this scenario, a compilation of facts and tips in having a conversation about sex education to teens is projected. The video is guided mainly by the tips provided by the Family Planning division of the Victorian State in Australia as seen in their website, http://www.betterhealth.vic.gov.au. It is evident that parents need motivation and a means in giving out the information that they have about sex education. Conservativeness has something to do with it but the researcher believes that not knowing what to say is a greater issue for them. Sex education is not just about sexual intercourse. However, being able to deliver the message effectively to students entails a lot of creativity and skills as for educators. This video production is intended to answer the Catholic Church's concern that parents should be the initial information-givers of their children. The researcher envisions that this project could be of help in preparing parents for the topic sex education.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts